A 96-well plate UV fluorometer based on micro fluorescence detector array and dynamic zero correction algorithm - Wang, Chuanliang; Geng, Xuhui; Gao, Yan; Zheng, Chao; Guan, Yafeng (Talanta (Oxford), 2023)
A 96-well plate UV fluorometer was developed and evaluated. Eight micro fluorescence detectors close to each other were used as detector array for 8 channels. Each detector employed an UV light emitting diode (LED) as light source and a photodiode (PD) with an amplifier circuit as optoelectronic detector. The optical paths of the detectors were designed by ray tracing method to avoid crosstalk between wells. Simultaneously scanning and detecting of 8 channels saves scanning time and improves detection efficiency. The scanning time of the 96-well plate was about 80 s. A dynamic zero correction algorithm was proposed to solve the problem of measurement accuracy reduction caused by the background fluorescence differences between plates and wells under irradiation of UV light. The measurement repeatability (RSD) for 1 μg/L 7-Diethylamino-4-methylcoumarin sample was 2.25%. Compared with the fixed zero correction method, the limit of detection (LOD), measurement repeatability, and average relative error were improved by 3.3, 2.7, and 4.5 times, respectively. The proposed method is robust and can be applied to different analysis systems. The developed fluorometer has great potential in high-throughput rapid detection of food safety and life sciences. [Display omitted] •A 96-well plate UV fluorometer was developed and evaluated.•Simultaneously scanning and detecting of 8 channels improves detection efficiency.•The dynamic zero correction algorithm improved the LOD and measurement accuracy.•The developed fluorometer has great potential in high-throughput rapid detection.